2011
DOI: 10.1007/s00415-010-5892-x
|View full text |Cite
|
Sign up to set email alerts
|

SMART syndrome: a late reversible complication after radiation therapy for brain tumours

Abstract: With intensified treatment leading to longer survival, complications of therapy for brain tumours are more frequently observed. Regarding radiation therapy, progressive and irreversible white matter disease with cognitive decline is most feared. We report on four patients with reversible clinical and radiological features occurring years after radiation for brain tumours, suggestive for the so called SMART syndrome (stroke-like migraine attacks after radiation therapy). All four patients (males, age 36–60 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(88 citation statements)
references
References 15 publications
(21 reference statements)
4
78
0
4
Order By: Relevance
“…Three patients had evidence of diffusion restriction, which completely resolved in 2 patients on follow-up (Tables 2 and 4). In Patients 2, 3, 4, and 5, subdural fluid collections were found in conjunction with parenchymal abnormalities that were improved (4), stable (2,3) or resolved (5) on follow-up imaging (Table 4). Acute radiographic abnormalities resolved completely in follow-up MRIs in Patients 1, 3, 5, and 6, whereas the remainder of patients had partial improvement on follow-up ( (presentation 1b), which were otherwise noted to be remarkably similar in radiographic appearance.…”
Section: Brain Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Three patients had evidence of diffusion restriction, which completely resolved in 2 patients on follow-up (Tables 2 and 4). In Patients 2, 3, 4, and 5, subdural fluid collections were found in conjunction with parenchymal abnormalities that were improved (4), stable (2,3) or resolved (5) on follow-up imaging (Table 4). Acute radiographic abnormalities resolved completely in follow-up MRIs in Patients 1, 3, 5, and 6, whereas the remainder of patients had partial improvement on follow-up ( (presentation 1b), which were otherwise noted to be remarkably similar in radiographic appearance.…”
Section: Brain Imagingmentioning
confidence: 99%
“…One potential mechanism describes radiation-induced vascular dysfunction secondary to endothelial cell injury leading to an abnormal autoregulatory state. [2][3][4] Alternatively, neuronal dysfunction resulting from a reduced threshold to cortical spreading depression in SMART patients has been suggested. 3,5 We propose that frequent electrographic seizure activity may be one mechanism causing similar prolonged reversible clinical symptoms and MRI findings.…”
Section: 3mentioning
confidence: 99%
“…3 Imaging is characteristic, usually demonstrating unilateral gyriform enhancement on MRI after 2-7 days. The imaging findings tend to resolve with neurologic recovery, 5,6 which typically occurs gradually over a period of 2-5 weeks. 3 However, most patients will have recurrent events, 4 and 45% of patients have incomplete neurologic recovery.…”
Section: How Would You Treat This Patient?mentioning
confidence: 99%
“…It has been proposed that the syndrome results from radiation-induced vasculopathy with endothelial injury and edema comparable to PRES; however, the predilection for the cortex is very different from PRES. 1,6 One study reported fluorodeoxyglucose PET imaging in 3 patients showing intense hypermetabolism in symptomatic regions that resolved on follow-up imaging. 5 Other hypotheses suggest that postradiation neuronal dysfunction, damage to the trigeminovascular system, migraine-like spreading depression, and ictal hyperperfusion may be contributors to the mechanism underlying SMART syndrome.…”
Section: How Would You Treat This Patient?mentioning
confidence: 99%
“…Thus, patients with multiple brain metastases are often selected for whole brain radiotherapy (WBRT) simply because it is the only option available. However, the most common problem reported after WBRT are chronic changes in the white matter, which are associated with stroke-like migraines (Kerklaan et al 2011;Black et al 2013;Armstrong et al 2014) , cognitive deficits (Shi et al 2009;Peiffer et al 2014;Forbes et al 2014) and dementia (DeAngelis et al 1989;D'Ambrosio et al 2007;Tallet et al 2012).…”
Section: Introductionmentioning
confidence: 99%